O espaço público da rua como síntese das reflexões críticas do urbano: encontro das diferenças no contexto da diversidade sócio-espacial contemporânea na RMBH - Giovana Helena de Miranda Monteiro (2012)
This work analyses the presence and meaning of public realm on the public spaces of a society. The spaces of everyday life are also places for encounters; where man creates and builds capacities related more to the human condition than to natural skills. Improving awareness of himself and of reality are competences favoured and motivated by theestablishment of relations with otherness. This study explores the participation of the sensible qualities (aisthesis) on the human engagement with space, especially around his everyday life activities, taken place out of the private realm, even if collectively accomplished. The fruition of the public sphere of the street by pedestrians and their elaboration of critical appreciation about its tangible and intangible aspects are understood as tools for the improvement of a specific relation: as far as engaging on the issues (res) related to the building of places and its laws, individuals and society build and refine their human condition.